Dental and oral manifestations of coeliac disease - a literature review - Eliza Jakubowska; Patrycja Łazicka; Magdalena Tuczyńska; Aleksandra Karolak; Joanna Jasińska (Kazimierz Wielki University, 2023)
Introduction  Coeliac disease is a genetic autoimmune disease of the digestive system. It is caused by permanent intolerance to gluten (a protein contained in wheat, rye, barley), which results in the atrophy of the intestinal villi in the small intestine and deficiency of nutrients in the body. It can also manifest itself with various pathologies within the teeth and oral mucosa.  Aim of the study  The purpose of the study is to present the symptoms of coeliac disease in oral cavity.  Materials and methods PubMed and Google Scholar medical databases were analyzed, operating with the following keywords: coeliac disease, oral cavity, manifestations, lesions, symptoms, oral health in as many configurations as needed. Twenty-eight related articles published during the last five years (2018-2023) were selected.  Results  In addition to the classic intestinal symptomatology, coeliac disease can also manifest itself in the oral cavity in the form of delayed tooth eruption, enamel defects, MIH, recurrent aphthous stomatitis or xerostomia. The etiology of the changes is still not clear, but studies show that they most likely arise as a result of impaired absorption of vitamins and minerals in the small intestine.  Conclusion The variety of symptoms of celiac disease makes it a significant diagnostic challenge. It is important to raise awareness among dentists about the symptoms of the disease because a quick diagnosis can prevent many complications.